Slight shading after anthesis increases photosynthetic productivity and grain yield of winter wheat (Triticum aestivum L.) due to the delaying of leaf senescence - Cai-long XU; Hong-bin TAO; Pu WANG; Zhen-lin WANG (Journal of Integrative Agriculture, 2016)
The solar radiation intensity and duration are continuously decreasing in the major wheat planting area of China. As a con-sequence, leaf senescence, photosynthesis, grain filling and thus wheat yield shall be affected by light deficiency. Therefore, two winter wheat (Triticum aestivum L.) cultivars, Tainong 18 (a large-spike cultivar) and Ji'nan 17 (a multiple-spike cultivar), were subjected to shading during anthesis and maturity under field condition in 2010–2011 and 2011–2012. Under the slight shading treatment (S1, 88% of full sunshine), leaf senescence was delayed, net photosynthesis rate (Pn) and canopy apparent photosynthesis rate (CAP) were improved, and thus thousand-kernel weight (TKW) and grain yield were higher as compared with the control. However, mid and severe shading (S2 and S3, 67 and 35% of full sunshine, respectively) led to negative effects on these traits substantially. Moreover, superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activities in flag leaf were significantly greater under slight shading than those in other treatments, while the malondialdehyde (MDA) content was less than that under other treatments. In addition, the multiple-spike cultivar is more tolerant to shading than large-spike cultivar. In conclusion, slight shading after anthesis delayed leaf senescence, enhanced photosynthesis and grain filling, and thus resulted in higher grain yield.